THE DEPICTION CHARACTER OF PATRIACHAL CULTURE IN THE MULAN MOVIE - Husaini; Muji Endah Palupi (BEGIBUNG: Jurnal Penelitian Multidisiplin, 2024)
The research object chosen in the film Mulan is because the narrative contained in the film Mulan discusses things that are very closely related to the phenomenon of patriarchal culture as is often the case in Indonesian society today. In this thesis there is a problem formulation, namely how patriarchal culture was formed and also the causes of the emergence of patriarchal culture in the film Mulan. Patriarchy is a structure that places men at the center compared to women. Patriarchal culture places women in a second position with limitations and is not allowed to exceed men's position as the main actor. This research is a qualitative descriptive method obtained through literature study. The conclusion of this thesis is that the writer concludes that Mulan's character in her behavior is able to fight discrimination and obstacles imposed on women by showing behavior as a leader, responsible, independent and brave enough to take risks. The writer hopes that similar research can use other approaches such as a feminist perspective and for filmmakers the writer hopes to raise the issue of gender equality so that it can help in building public awareness of the importance of gender equality.